2021
DOI: 10.1073/pnas.2010083118
|View full text |Cite
|
Sign up to set email alerts
|

Dog domestication and the dual dispersal of people and dogs into the Americas

Abstract: Advances in the isolation and sequencing of ancient DNA have begun to reveal the population histories of both people and dogs. Over the last 10,000 y, the genetic signatures of ancient dog remains have been linked with known human dispersals in regions such as the Arctic and the remote Pacific. It is suspected, however, that this relationship has a much deeper antiquity, and that the tandem movement of people and dogs may have begun soon after the domestication of the dog from a gray wolf ancestor in the late … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
96
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(105 citation statements)
references
References 72 publications
(113 reference statements)
3
96
0
6
Order By: Relevance
“…Archaeozoologists and paleogeneticists now suggest that the domestic dog was derived originally from Pleistocene wolves sometime between 40,000 and 15,000 years ago during the Last Glacial Maximum (LGM), possibly in more than one region of Europe and/or Asia (2)(3)(4)(5)(6)(7). Wolves were therefore the first animals to be domesticated by humans, preceding the domestication of food or livestock species, such as sheep and goats, by a minimum of 4-5 thousand years.…”
Section: The Origin(s) Of the Dogmentioning
confidence: 99%
“…Archaeozoologists and paleogeneticists now suggest that the domestic dog was derived originally from Pleistocene wolves sometime between 40,000 and 15,000 years ago during the Last Glacial Maximum (LGM), possibly in more than one region of Europe and/or Asia (2)(3)(4)(5)(6)(7). Wolves were therefore the first animals to be domesticated by humans, preceding the domestication of food or livestock species, such as sheep and goats, by a minimum of 4-5 thousand years.…”
Section: The Origin(s) Of the Dogmentioning
confidence: 99%
“…In particular, when focusing on the total abundance and pattern of carbohydrate-active enzymes (CAZymes), we found that the GM of Solarolo dogs was generally comparable with that of modern dogs, possessing a higher load of reads assigned to CAZymes and a dog-like overall compositional profile of CAZyme families (Figure S6). The domestication of dogs has undoubtedly represented a major step in recent canine evolutionary history, requiring progressive adaptation steps to multiple and rapid ecological transitions, as a result of sharing life and establishing a close mutualistic relationship with humans (Perri et al, 2021). To specifically examine the canine GM components responding to domestication and to subsequent ecological transitions, we applied the BDTT (b-diversity through time) method, which was previously developed to discriminate the evolutionary dynamics of GM components in response to host phylogeny or diet (Groussin et al, 2017).…”
Section: Phylosymbiosis and Gut Microbiome Response To Canine Phylogeny And The Domestication Processmentioning
confidence: 99%
“…Compared with their wild counterparts, domesticated animals show relevant variations in the GM structure (McKenzie et al, 2017;Metcalf et al, 2017;Reese et al, 2021), and this is likely the result of an adaptive response to changes in diet, lifestyle, and physiology (Alberdi et al, 2016;Coelho et al, 2018). Dogs are one of the best-known examples of domestication (Thalmann et al, 2013;Botigué et al, 2017;Bergströ m et al, 2020;Perri et al, 2021). They are in fact the first domesticated species and the only known animal to enter into a domestic relationship with humans before the end of Pleistocene.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After millennia of constructing niches based on hunting, gathering, and foraging, a range of communities in diverse parts of the world embarked on trajectories of food production which in some instances led to the emergence of complex societies, urbanism, and empires, sowing the seeds for our current globalization. Thanks to intensive zooarcheology and genomics research, it is now common knowledge that, apart from dog domestication within hunter–gatherers societies around 23,000 years Before Present (BP) terminus post quem ( Perri et al, 2021 ), the domestication of globally important livestock animals occurred within sedentary communities engaged in early agriculture in three independent cradles. The oldest of these is located in Southwest Asia where cereals (wheat, barley), legumes (pulse, peas, lentils), and fruits (figs) were domesticated between 12,000 and 10,000 BP, followed by sheep, goat, pigs, and cattle between 10,500 and 10,000 BP ( Colledge et al, 2013 ).…”
mentioning
confidence: 99%